Holiness in the Poetries of Philip Larkin (Global Journal of Human-Social Science, 2012)
Philip Arthur Larkin 9 August 1922 2 December 1985 is widely regarded as one of the great English poets of the latter half of the twentieth century His first book of poetry The North Ship was published in 1945 followed by two novels Jill 1946 and A Girl in Winter 1947 but he came to prominence in 1955 with the publication of his second collection of poems The Less Deceived followed by The Whitsun Weddings 1964 and High Windows 1974 He contributed to The Daily Telegraph as its jazz critic from 1961 to 1971 articles gathered together in All What Jazz A Record Diary 1961 71 1985 book cover above and he edited The Oxford Book of Twentieth Century English Verse 1973 He was the recipient of many honors including the Queen s Gold Medal for Poetry He was offered but declined the position of poet laureate in 1984 following the death of John Betjeman
Keywords: holiness of the drab; of the quiet passion and persistence of submerged lives; of the heroism of compromise with frustration; passionate engagement wi